Estimated Incidence of Symptomatic Lyme Borreliosis Cases in Lublin, Poland in 2021 - Emily Colby; Julia Olsen; Frederick J. Angulo; Patrick Kelly; Kate Halsby; Andreas Pilz; Urszula Sot; Tomasz Chmielewski; Katarzyna Pancer; Jennifer C. Moïsi; Luis Jodar; James H. Stark (Microorganisms, 2023)
Lyme borreliosis (LB), the most common tick-borne disease in Europe, is endemic to Poland. Despite public health surveillance with mandatory reporting of LB cases by physicians and laboratories, many symptomatic LB cases are not included in surveillance in Poland. We estimated the extent of the under-ascertainment of symptomatic LB cases via surveillance in the Polish province of Lublin to better understand Poland’s LB burden. The number of incident symptomatic LB cases in Lublin in 2010 was estimated from two seroprevalence studies conducted among adults in Lublin, as well as estimates of the proportion of asymptomatic LB cases and the duration of LB antibody persistence. The estimated number of incident symptomatic LB cases was compared to the number of surveillance-reported cases in Lublin to derive an under-ascertainment multiplier. This multiplier was applied to the number of surveillance-reported cases in 2021 to estimate the number and population-based incidence of symptomatic LB cases in Lublin in 2021. We estimate that there are 5.9 symptomatic LB cases for every surveillance-reported LB case in Lublin. Adjusting for under-ascertainment, the estimated number of symptomatic LB cases in Lublin in 2021 was 6204 (population-based incidence: 467.6/100,000). After adjustment for under-ascertainment, the incidence of symptomatic LB in Lublin, Poland, is high.